SUPRA-SUBDUCTION ORIGIN OF THE NIDAR OPHIOLITIC SEQUENCE, INDUS SUTURE ZONE, LADAKH, INDIA: EVIDENCE FROM MINERAL CHEMISTRY OF UPPER MANTLE ROCKS - Sachan, Himanshu K. (Ofioliti, 2001)
The ultramafic rocks of Nidar ophiolitic sequence in the eastern part of the Ladakh (NW Himalaya) have been studied combining petrography and mineral chemistry data. The ultramafic rocks mainly consist of spinel-harzburgite and spinel-dunite, that are intruded by spinel-bearing pyroxenites. The modal and chemical composition of minerals in harzburgite indicates a strongly-depleted nature consistent with a residual origin after the extraction of basaltic melt by single or multiple partial melting events. In contrast, dunite was probably formed as a consequence of interaction between harzburgite and migrating melt(s), after the partial melting events. This is well corroborated by the petrographical and chemical evidence, e.g., the growth of secondary mineral aggregates and the large chromite component in the spinels.The mineral chemistry suggests that the melts percolating and interacting with harzburgite were rich in MgO and NiO and deficient in CaO, Al2O3, and TiO2. In particular, the low Ti content shown by clinopyroxenes and spinels (which are cumulus phases in pyroxenites and secondary neoblastic phases in peridotites), in association with high Cr# (> 60) exhibited by all the spinels, are consistent with parent melt of boninitic affinity. These melts are typical of island arc environment. Therefore, this infers that the ultramafic units of Nidar ophiolite underwent melt percolation in a supra-subduction tectonic environment related to fore-arc setting.